1999
DOI: 10.1074/jbc.274.5.2597
|View full text |Cite
|
Sign up to set email alerts
|

Association of the p75 Neurotrophin Receptor with TRAF6

Abstract: In addition to the Trk tyrosine kinase receptors, neurotrophins also bind to a second receptor, p75, a member of the tumor necrosis factor receptor superfamily. Several signaling pathways have been implicated for p75 in the absence of Trk receptors, including induction of NF-B and c-Jun kinase activities and increased production of ceramide. However, to date, the mechanisms by which the p75 receptor initiates intracellular signal transduction have not been defined. Here we report a specific interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
191
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(202 citation statements)
references
References 41 publications
9
191
2
Order By: Relevance
“…We expected the resulting construct to compete effectively for binding to NGF against the endogenous p75 but be incapable of its own signaling. To facilitate the detection of the chimeric receptor, an HA tag was placed at the N terminus of rat p75 cDNA after the signal peptide sequence (Khursigara et al, 1999). Because the adenovirus contains GFP under a separate promoter (Fig.…”
Section: Results P75 Protein Is Required For Ngf-dependent Apoptosis mentioning
confidence: 99%
“…We expected the resulting construct to compete effectively for binding to NGF against the endogenous p75 but be incapable of its own signaling. To facilitate the detection of the chimeric receptor, an HA tag was placed at the N terminus of rat p75 cDNA after the signal peptide sequence (Khursigara et al, 1999). Because the adenovirus contains GFP under a separate promoter (Fig.…”
Section: Results P75 Protein Is Required For Ngf-dependent Apoptosis mentioning
confidence: 99%
“…72 The presence of TRAF2 or TRAF6 proteins in the cytoplasm of motor neurons sequesters the death receptors, aiding in survival of the neuron. 73,74 However, E2F-1 located in the cytoplasm may induce complex formation with TRAF proteins to impede their function, thus releasing death receptors that could now induce cell death via the p75 NTR pathway or other death receptor pathways. [72][73][74] There is indeed precedence to the interactions of E2F-1 with the TRAF proteins in other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 However, E2F-1 located in the cytoplasm may induce complex formation with TRAF proteins to impede their function, thus releasing death receptors that could now induce cell death via the p75 NTR pathway or other death receptor pathways. [72][73][74] There is indeed precedence to the interactions of E2F-1 with the TRAF proteins in other cell types. 72 This hypothesis warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…32 Research in the past few years has revealed that the p75 NTR is coupled to both JNK and NF-kB activation through the tumor necrosis factor receptorassociated factor-6 (TRAF6) protein. 33 TRAF6 is one of the six TRAF family members identified to date and is expressed in most tissues, including the CNS. A dominant negative mutant of TRAF6 effectively inhibits NF-kB activation through the p75 NTR , while not affecting activation through trkA.…”
Section: Growth Factor Signalingmentioning
confidence: 99%